Competitors' envy, gamers' pride: An exploration of gamers' divergent behavior. Issue 6 (27th February 2021) - Sharma, Rashmini; Singh, Gurmeet; Sharma, Shavneet
Abstract: Cheating in games has existed since the beginning of video games. The landscape of gaming and cheating has changed profoundly with its migration to the online environment. This study aims to investigate the unethical behavioral intention of online gamers. The Theory of Planned Behavior and Social Comparison Theory is used to develop a comprehensive framework to understand gamers' cheating intention. This study employs a quantitative approach to collect data from 404 gamers using a random sampling technique. Results show that attitude, subjective norms, perceived behavioral control, hedonic motivation, and benign envy influences gamers' online cheating intention. Online cheating intention was found to influence online cheating behavior positively. Looking at the moderating effect of ethical judgment, this study revealed that ethical judgment dampens the positive relationship between attitude, benign envy, and perceived behavioral control on gamers' online cheating intention. This study is the first to explore the impact of different types of envy on divergent gaming behavior. It contributes to the literature by generating insights into an under‐researched area of divergent online gaming behavior.